The Reign of Sultan Abdulaziz in the American Press - Ercan KARAKOÇ; Gökhan DURAK (Gazi Akademik Bakış)
Sultan Abdulaziz ascended the Ottoman throne in a difficult period of political and economic crisis. During the 19th century, the empire was on the point of disintegration due to rebellions in the Balkans, especially in the region of Wallachia-Moldavia. The state’s finances almost collapsed. Internally, an important opposition front formed with the influence of the Young Ottomans. This opposition grew stronger over time within the military and political bureaucracy and played a critical role in Abdulaziz’s detohrement and Murad V becoming the sultan. In this study, the important events that took place in the Abdulaziz period and the developments following his dethronement are examined through some American newspapers and American State Department documents. The last period of the Empire was examined with different documents by giving a new perspective to the Ottoman history.